IMPLEMENTATION OF CHARACTERISTICS IN ELEMENTARY SCHOOL STUDENTS - Nur Widyawati; Shirly Rizki Kusumaningrum; Radeni Sukma Indra Dewi (Jurnal Darma Agung, 2022)
Implementing habituation to support the realization of good character in students is a must for institutions. In addition to being intelligent in knowledge, students are expected to have good character. The system of inculcating character values in a person is applied in daily actions or behavior through habituation, advice, teaching and guidance. Every child has good potential from birth, but this potential must continue to be honed and socialized properly so that the character of each child is formed and developed. The method used in this paper is a literature review with a descriptive qualitative approach to describe the results of observations and literature studies. Based on the literature review and the results of these observations, it is found that the implementation of habituation in character planting is the right alternative, fast, and it is important to realize students who are smart and have superior character. Habituation takes various forms such as religious habituation, caring for the environment, manners, as well as in self-development.